Modern chatbot systems: a technical review - Abbas Saliimi, Lokman; M. A., Ameedeen (Springer Nature Switzerland, 2019)
Chatbot (abbreviated Chatting Robot) is a computer sys- tem that allows human to interact with computer using Natural Human Language. This paper intents to present a technical review of ve mod- ern chatbot systems namely DeepProbe (July, 2017), Alime (August, 2017), SuperAgent (August, 2017), MILABOT (November, 2017) and RubyStar (December, 2017). Review elements are architectural design and domain/case study implementation with performance evaluation. Architectural design review will cover topic surrounding chatbot's knowl- edge domain, response generation, text processing and machine learning model, while implementation review will cover dataset usage (mainly to- wards machine learning model training) and evaluation strategy towards analyzing the quality level of chatbot's response. A summarize table of all reviewed elements is shown at the end of this paper together with discussion on our insight regarding reviewed elements. This paper will concludes with our review on future roadmap for modern chatbot design.